1999
DOI: 10.2307/1383212
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic Variation in Skull Shape of Thrichomys apereoides (Rodentia: Echimyidae)

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. American Society of Mammalogists is collaborating with JSTOR to digitize, preserve and extend access to Journal of Mammalogy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 22 publications
(6 reference statements)
0
20
0
1
Order By: Relevance
“…niloticus have longer zygomatic arches with a sharper-angled leading edge that may possibly allow for greater masseter muscle attachments (Satoh and Iwaku 2004). It has been argued that the shape of certain bony structures can be altered by the atrophy or hypertrophy of attached muscles (Monteiro et al 1999). Nevertheless, other studies reported on associations between sexual differences and competition between males (Darwin 1874), food resources (Schoener 1967), diet selection and intake rates (Yamada and Kimmel 1991), habitat use (Clutton-Brock et al 1987), growth rates, and strategies (Zelditch et al 1992), in addition to variation in individual reproductive success (Weckerly 1998).…”
Section: Discussion Sexual Dimorphismmentioning
confidence: 99%
See 1 more Smart Citation
“…niloticus have longer zygomatic arches with a sharper-angled leading edge that may possibly allow for greater masseter muscle attachments (Satoh and Iwaku 2004). It has been argued that the shape of certain bony structures can be altered by the atrophy or hypertrophy of attached muscles (Monteiro et al 1999). Nevertheless, other studies reported on associations between sexual differences and competition between males (Darwin 1874), food resources (Schoener 1967), diet selection and intake rates (Yamada and Kimmel 1991), habitat use (Clutton-Brock et al 1987), growth rates, and strategies (Zelditch et al 1992), in addition to variation in individual reproductive success (Weckerly 1998).…”
Section: Discussion Sexual Dimorphismmentioning
confidence: 99%
“…In addition, shape variation occurring during ontogeny was estimated by multivariate regression analysis (Zar 1996;Monteiro et al 1999) of partial warps (i.e., total shape matrix) on centroid size and age categories. Since our results (see later) revealed the absence of sexual dimorphism in size (i.e., centroid size) in Ar.…”
Section: Age Classesmentioning
confidence: 99%
“…Morphological integration can be signiWcantly modiWable within a single pattern of development (Zelditch Fig. 4 Post-metamorphic ontogenetic transformations in cranial shape of each species, calculated by multivariate regression of shape on size, and illustrated as a thin plate spline deformation grid 1988; Zelditch and Carmichael 1989;Cane 1993;Monteiro et al 1999) so further inspection of the forces producing a speciWc pattern of covariation between and among skull parts, including developmental, functional and biomechanical factors, will be needed to provide more information on the common factors shaping the newt skull during postmetamorphic growth.…”
Section: Post-metamorphic Modeling Of the Triturus Skullmentioning
confidence: 99%
“…We chose skull morphology (size and shape) as a surrogate of overall morphological diversity as it is associated with the main sensory systems related to environmental perception and reflects changes in the dietary and ecological interactions across populations (Klaczko, Sherratt, & Setz, 2016;Monteiro, Lessa, & Are, 1999;Nogueira, Peracchi, & Monteiro, 2009). First, we analyzed nine species (shrews, moles, and rodents) distributed over a wide altitudinal range and with distinct ecological attributes to assess whether phenotypic divergence is a common phenomenon in small mammals and whether it shows consistent parallel patterns.…”
Section: Introductionmentioning
confidence: 99%